KESANTUNAN BERBAHASA GURU BAHASA INDONESIA DALAM PROSES BELAJAR MENGAJAR DI SMP NEGERI 1 PADANG GANTING - Rahman, Yose; Agustina, Agustina (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ This The purpose of this research is (1) to describe of the said Indonesian language teacher in the process of teaching and learning in SMPN 1 Padang Ganting, (2) to describe the principle of good manners speaking Indonesian language teacher in the process of teaching and learning in SMPN 1 Padang Ganting, and (3) to describe the context of good manners speaking Indonesian language teacher in the process of teaching and learning in SMPN 1 Padang Ganting. This type of research is a qualitative with descriptive method. The technique used a records. The findings of this research is (1) there are five types of acts said that teachers use in the process of teaching and learning, that is (a) directive, (b) representative, (c) declaration, (d) expressive, and (e) commisive. (2) There are four kind of maxims good manners used, that is (a) wisdom, (b) the deal, (c) praise, and (d) humility. (3) the context good manners are used based on several components, that is (a) setting, (b) participant, (c) end, (d) act sequences, (e) keys, (f) instrumentalies, (g) norm, and (h) genre.Â Kata kunci: kesantunan berbahasa, tindak tutur, guru